Xylanase and Direct-Fed Microbials (DFM) Potential for Improvement of Live Performance, Energy Digestibility, and Reduction of Environmental Microbial Load of Broilers - Nusairat, Basheer; Wang, Jeng-Jie (Frontiers in Veterinary Science, 2020)
The challenge of identifying alternatives to subtherapeutic levels of antibiotic growth promoters (AGP) in animal feed has led to increased interest in feed additives such as exogenous enzymes and direct-fed microbials (DFM). Six corn soy-based dietary treatments were designed to investigate the effect of high-efficiency xylanase alone, Bacillus spp. probiotics alone, and their combination vs. a commonly used antibiotic growth promoter (bacitracin methylene disalicylate; BMD) on live performance and environmental Clostridium perfringens load of broiler chickens with eight replicate pens per treatment. Diets were as follows: standard diet (positive control; PC); 130 kcal/kg reduced-energy diet (negative control; NC); NC with xylanase (NC + Xy); NC with probiotics (NC + Pro); NC with xylanase and probiotics mix (NC + XyPro); and NC with BMD (NC + BMD). Data were analyzed as one-way ANOVA. At 35 and 42 days, birds fed with NC + XyPro and NC + BMD were heavier (P < 0.05) than birds fed with NC. Improvement in feed conversion ratio (FCR) (P = 0.0001) was observed from 1 to 42 days by 3 points in both NC + XyPro and NC + BMD compared to NC. The NC + XyPro reduced lesion scores by 66% compared to PC and NC. Litter C. perfringens cell count was reduced by 16% with supplementation of XyPro or BMD. It can be concluded that a blend of xylanase (10 XU/g feed) and Bacillus spp. [1 × 105 colony forming units (CFU)/g feed] can be used as an alternative to AGP in low-energy broiler diets.